2021
DOI: 10.1001/jamanetworkopen.2021.11336
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics of e-Cigarette Use Behaviors Among US Youth, 2020

Abstract: Key Points Question What are the characteristics of current (past 30-day) e-cigarette use among US high school and middle school students in 2020? Findings This survey study of 14 531 students found that among the 19.6% of high school students and 4.7% of middle school students who currently used e-cigarettes in 2020, 38.9% of high school users and 20.0% of middle school users self-reported use on 20 to 30 days during the past 30 days, and most reported fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 18 publications
1
75
0
Order By: Relevance
“…Prior to the COVID-19 pandemic, the U.S. was engulfed in an epidemic of e-cigarette use among youth and young adults, 9 and EVALI (e-cigarette and vaping associated lung injury) cases were emerging across the U.S. 10 However some studies have shown declines in e-cigarette use among youth and young adults since the start of the COVID-19 pandemic, which may be due to a number of factors including greater perceived risk of e-cigarette use and diminished access to e-cigarettes. 11 - 13 Yet, these same studies show that e-cigarette use remains prevalent, and despite declines in use, some youth and young adults have increased their use, too, amid COVID-19. 11 - 13 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Prior to the COVID-19 pandemic, the U.S. was engulfed in an epidemic of e-cigarette use among youth and young adults, 9 and EVALI (e-cigarette and vaping associated lung injury) cases were emerging across the U.S. 10 However some studies have shown declines in e-cigarette use among youth and young adults since the start of the COVID-19 pandemic, which may be due to a number of factors including greater perceived risk of e-cigarette use and diminished access to e-cigarettes. 11 - 13 Yet, these same studies show that e-cigarette use remains prevalent, and despite declines in use, some youth and young adults have increased their use, too, amid COVID-19. 11 - 13 …”
Section: Introductionmentioning
confidence: 98%
“… 11 - 13 Yet, these same studies show that e-cigarette use remains prevalent, and despite declines in use, some youth and young adults have increased their use, too, amid COVID-19. 11 - 13 …”
Section: Introductionmentioning
confidence: 98%
“…Among current users, more than 8 in 10 reported using e-cigarettes that contain flavoring and flavoring agents. Although the use of fruit-flavored e-cigarettes was common among e-cigarette users in 2020, the findings from studies in the US also highlight the prominence of menthol e-cigarette use, which accounted for nearly half of flavored, pre-filled pod or cartridge users and a quarter of flavored disposable product users 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Further, the majority of study participants reported either no change, or more vaping since the COVID-19 outbreak, which suggests that these findings are still applicable even in the context of the pandemic. At the time of the pandemic, adolescents and young adults frequently interacted with friends in social gatherings in some communities (25), where they could obtain e-cigarettes from friends -the most common source among US Youth (12,26).…”
Section: Discussionmentioning
confidence: 99%